The impact of Gibe III hydroelectric dam on the situation of livestock diseases with particular emphasis on bovine trypanosomosis in Southern Ethiopia - Solomon Mekuria; Hoges Ashenafi; Nigatu Kebede; Tadesse Eyasu; Saifemichael Ushecho; Getachew Terefe (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
This study was initiated to explore the impact of Gibe III dam on the situation of livestock diseases with emphasis on trypanosomosis in upstream and downstream districts. Focus group discussions with 15 groups each with 6-20 members were conducted using participatory research approach. Data were collected through simple ranking, proportional piling and matrix scoring. Level of agreement among groups analyzed was determined by Kendell's coefficient concordance (W). Proportional piling revealed that bovine trypanosomosis ranked first followed by blackleg and anthrax. Study participants identified livestock diseases by name and described the most salient features of each disease. Community perception on clinical signs, disease transmission, seasonality, of tsetse vectors, socio-economic impacts, control methods commonly of trypanosomosis was in a good agreement (W > 0.38***; p<0.001). Livestock disease outbreaks and the challenge from tsetse and trypanosomosis were perceived significantly reduced after dam construction in the upstream villages whereas dam construction and the artificial lake created thereof had little impact on the situation of trypanosomosis and the tsetse population in the downstream villages along the Omo river. Therefore, any tsetse and trypanosomosis control program should take into account the basic differences in the two sites and accordingly provide customized services.